Penggambaran Dunia Pulau Bali Tahun 1930 M dalam Novel Rihlatu Jāwā Al-Jamīlatu Karya Sholeh bin Ali Al-Hamid: Sastra Perjalanan Carl Thompson - Hermawati Putri Dian Insani; Hindun Hindun (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
This study aims to reveal the reportation of the world of Bali island in the novel Rihlatu Jāwā Al-Jamīlatu by Sholeh bin Ali Al-Hamid. This novel tells about the journey of Arabic literati in Indonesia in 1930 AD, one of which is the island of Bali.  The depiction of the world in this study is revealed with carl thompson's theory of Travel Literature and the research method used is a descriptive qualitative research method. Based on the analysis that has been carried out, the depiction of the world in this novel tends to be objective, because Al-Hamid describes the island of Bali as it is, namely geographical location, weather, city atmosphere, natural landscapes, and tourist attractions. In addition, the Balinese society described by Al-Hamid is a traditional society that maintains traditions and customs.